Prognostic value of near-infrared spectroscopy in hypoxic-ischaemic encephalopathy - Catarina Oliveira Pereira; Andrea Dias; Inês Nunes Vicente; Joana Teresa Pinto; Carla Marques; Alexandra Dinis; Carla Pinto; Leonor Carvalho (Elsevier, 2021)
Introduction: Despite treatment with hypothermia, 40% of newborns with hypoxic-ischaemic encephalopathy die or suffer moderate to severe disability. Near-infrared spectroscopy (NIRS) could be a useful, non-invasive tool to establish the prognosis. Objectives: To evaluate the prognostic value of NIRS in predicting neurodevelopmental outcomes at 18-36 months in newborns with hypoxic-ischaemic encephalopathy, and to establish the time points and cut-off values of regional cerebral oxygen saturation that exhibit the strongest correlation to these outcomes. Patients and methods: The study included all term newborns with hypoxic-ischaemic encephalopathy managed with hypothermia and NIRS between 2013 and 2016. We established 3 outcome categories: normal neurodevelopment, moderate disability and severe disability. Results: The sample comprised 28 newborns (median gestational age, 39 weeks; median birth weight, 3195 g). The median regional cerebral oxygen saturation increased from 65% to 85% at 48 h post birth. Neurodevelopmental outcomes were normal in 28.6%, while 35.7% developed moderate disability and 35.7% severe disability; 3 patients died. We found a statistically significant difference between groups at 48 h (P = .005) and after hypothermia (P = .03), with higher values in patients with disability. When we compared patients with severe disability group with the other groups, we found a statistically significant area under the ROC curve at 48 h of 0.872 (P = .001) applying a regional cerebral oxygen saturation cutoff of 83.5%. After hypothermia, regional cerebral oxygen saturation values below 66.0% (AUC, 0.794; P = .017) predicted normal development, while values above 82% (AUC, 0.881; P = .001) predicted severe disability. Conclusions: NIRS seems to be a valuable tool to predict neurodevelopmental outcomes in patients with hypoxic-ischaemic encephalopathy, even after hypothermia, with higher cerebral oxygen saturation values in patients with disability. Resumen: Introducción: A pesar del tratamiento con hipotermia, el 40% de los neonatos con encefalopatía hipóxico-isquémica fallecen o sufren discapacidad moderada-grave. La espectroscopia cercana al infrarrojo (NIRS) se propone como una herramienta útil y no invasiva para establecer el pronóstico. Objetivos: evaluar el valor pronóstico de la NIRS en el resultado del neurodesarrollo entre los 18-36 meses en neonatos con encefalopatía hipóxico-isquémica y establecer el tiempo y los puntos de corte de la saturación cerebral de oxígeno que mejor se relacionan con el pronóstico. Pacientes y métodos: Se incluyeron todos los neonatos a término con encefalopatía hipóxico-isquémica, sometidos a hipotermia y NIRS, entre 2013−2016. Con respeto al resultado, se constituyeron tres grupos: neurodesarrollo normal, discapacidad moderada y grave. Resultados: Se incluyeron 28 neonatos (edad gestacional mediana: 39 semanas; peso al nacimiento mediano: 3195 gramos). La saturación cerebral de oxígeno tendió a aumentar desde una mediana de 65% hasta 85%, a las 48 horas de vida. El resultado del neurodesarrollo fue normal en 28,6%, el 35,7% adquirió discapacidad moderada y el 35,7% discapacidad grave (tres fallecieron). Se halló una diferencia estadística entre los grupos a las 48 horas (p = 0,005) y después de la hipotermia (p = 0,03), con valores más altos en los pacientes con discapacidad. Teniendo en cuenta el grupo con discapacidad grave frente a los otros, la curva de ROC a las 48 horas resultó en un área debajo de la curva (AUC) significativa de 0,872 (p = 0,001), con un punto de corte de saturación cerebral de oxígeno de 83,5%. Después de la hipotermia, los valores de saturación cerebral de oxígeno por debajo del 66,0% (AUC 0,794; p = 0,017) predijeron el desarrollo normal mientras que valores por encima del 82% (AUC 0,881; p = 0,001) predijeron discapacidad grave. Conclusiones: El NIRS parece constituir una herramienta útil en la predicción del resultado del neurodesarrollo de pacientes con encefalopatía hipóxico-isquémica, incluso después de la hipotermia, con valores más altos de saturación cerebral de oxígeno en pacientes con discapacidad.